Understanding ferrite deformation caused by austenite to martensite transformation in dual phase steels. (September 2021) - Atreya, Vibhor; Bos, Cornelis; Santofimia, Maria J.
Abstract: During the production of DP steels, the volume expansion and shape change accompanying the austenite to martensite transformation is accommodated by the deformation of surrounding ferrite grains. The extent of the deformation in ferrite grains ultimately affects the mechanical properties of DP steels. Using electron backscatter diffraction measurements, this study identifies the characteristics of martensite which govern the extent of transformation induced deformation of ferrite grains. It was found that small austenite grains tend to transform into martensitic variants having a close-packed plane parallel relationship with adjacent ferrite grains, thus achieving relatively easy slip transmission and resulting in a long-range deformation of ferrite grains. Ferrite grains can also exhibit a short-range deformation limited to the vicinity of the ferrite/martensite interface, which is primarily governed by martensite carbon content.